KECERNAAN NUTRIEN PAKAN TEPUNG DAUN MURBEI PADA SAPI PERANAKAN ONGOLE - Duta Setiawan; Komang G Wiryawan (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The research was conducted to study the ability of mulberry leave meal addition concentrates on the digestibility nutrient of Ongole Grade. This experiment used a randomized block design, with 4 treatments and 4 blocks. Treatments consisted of P1 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate complete), P2 (native grass and concentrate feed in the form of mulberry leaves meal and corn concentrate), P3 (native grass and concentrate feed in the form of mulberry leaves meal and rice bran concentrate), P4 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate tapioca waste). The experiment was conducted for 4 months with the adaptation periods for 2 weeks. Parameters measured were digestibility of dry matter (KCBK) and organic matter (KCBO), . The results showed that the mulberry leave meal addition on different concentrate did significantly (P<0,05) on digestibility of dry matter (KCBK) and organic matter (KCBO). It is concluded that based on the nutrient digestibility, mulberry leave meal concentrate can be combined with a single concentrate such as corn, cassava waste meal or complete concentrate. Keywords: mulberry leave meal, ongole grade cattle, digestibility of dry matter and organic matter.